2021
DOI: 10.5489/cuaj.7271
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and predictors of delayed recognition of iatrogenic ureteric injuries

Abstract: Introduction: Although intraoperative iatrogenic ureteric injuries (IUI) are rare, significant consequences can occur if they are unrecognized at the time. The focus of our study is to characterize the associated morbidity and identify predictors of delayed recognition of IUI. Methods: Sunnybrook Health Sciences Centre Research Ethics Board approved the study. Patients with a diagnosis of IUI between 2002 and 2020 were identified through an institutional electronic medical record system. Data pertaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Similarly, we found the incidence of delayed recognition of IUI in our institutional series of 103 patients to be 20%. 4 Herein, we found that patients who had a delayed recognition of IUI were approximately 2 times more likely to develop hydronephrosis or stricture and 3 times more likely to develop renal impairment than those with immediately diagnosed IUI. Total costs were approximately 2 times higher in those with a delayed diagnosis of IUI.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Similarly, we found the incidence of delayed recognition of IUI in our institutional series of 103 patients to be 20%. 4 Herein, we found that patients who had a delayed recognition of IUI were approximately 2 times more likely to develop hydronephrosis or stricture and 3 times more likely to develop renal impairment than those with immediately diagnosed IUI. Total costs were approximately 2 times higher in those with a delayed diagnosis of IUI.…”
Section: Discussionmentioning
confidence: 69%
“…To validate this definition of IUI, we compared the number of patients identified using this approach at our institution to those identified in our electronic medical records system and noted an agreement of 103 patients. 4…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients presenting postoperatively may experience signs and symptoms of renal obstruction, such as flank pain, a febrile postoperative course, ileus, a urine leak, and a rise in serum creatinine [20] . Delayed UI detection is associated with significantly higher rates of 90-d readmission, sepsis, urinary fistula, acute renal injury, and death [19] , [21] . Furthermore, postoperative UI detection typically requires temporary urinary diversion and multiple procedures or operations for definitive management, which has a considerable negative impact on patient mental health, patient-partner relationships, employment, litigation, and health care costs [17] , [20] , [21] .…”
Section: Discussionmentioning
confidence: 99%
“…As the number of laparoscopic surgeries increases, a higher proportion of iatrogenic ureteral injuries postoperatively are found 1 . More than half of these injuries are postoperatively recognized in response to symptoms such as abdominal pain, fever, or nausea 2 . Although immediate surgical repair of iatrogenic ureteral injuries is usually successful, delayed surgical repair can be challenging and may require the expertise of a urologist 1 .…”
Section: Introductionmentioning
confidence: 99%